Impact of boron foliar fertilization on annual fluctuation of B in sweet cherry leaves and fruit quality - P. T. Nagy; T. Thurzó; Z. Szabó; J. Nyéki (International Journal of Horticultural Science, 2008)
The goal of the study was to examine response of sweet cherries (Prunus avium L.) to boron (B) fertilization. The experiment was conducted during 2005-2007 in West Hungary on mature cv. `Germersdorfi 3' grafted on Prunus mahaleb rootstock.